Topicalização: um estudo histórico sobre a ordem dos constituintes em cartas oficiais da Paraíba dos séculos XVIII e XIX - Cavalcante, Maria Alba Silva (2011)
This paper aims to describe and analyze the topic sentences in official letters of Paraiba from the eighteenth and nineteenth centuries. The topicalization is currently considered a characteristic phenomenon of the Portuguese language spoken in Brazil, as shown Pontes (1987), however, it is noteworthy that this phenomenon already appears in Portuguese in Brazil (PB) since the late eighteenth century, as the corpus investigated . This observation leads to some questions about the motives that could be related to disruption of the order of the sentence by topicalization, and the disruption would be linked to specific situations in these letters. To support this theory research were two basic lines of research: on the one hand, historical studies of language focused on the discursive traditions, the Pragmatic proposed by the German philologists, proposed by Kabatek (2006), on the other hand, studies of Eunice Pontes (op.cit), Castilho (2001), Gibrail (2007) on topicalization in PB and PE (European Portuguese). Besides the theoretical framework along these lines, investigations were made in other literatures, dealing not only topicalization, but also the arrangement of words in the sentence, and postulate that the canons in the eighteenth and nineteenth centuries. These are cited historical grammars, such as Grammar Philosophical Barbosa (1822), which discusses the pattern of the Portuguese language in that period. This study is qualitative, quantitative and descriptive and interpretive, that this procedure allowed the analysis of 203 letters. The methodology adopted in this research consisted in the separation of these texts, according to the presence or absence of topicalization, realized always from reading the first paragraph. Were subsequently evaluated and described instances of topicalized structures. The study points to a lower frequency of theses structures, in lieu of not topicalized structures due to various reasons, as the communication situation described in these manuscripts.